EFFECT OF EFFLEURAGE MASSAGE ON BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS - Rukmawati, Sefrina; Astutik, Puji (LPPM STIKes SATRIA BHAKTI NGANJUK, 2022)
One of the massages that can launch breast milk production is efflurage massage. The purpose of this study was to determine the effect of efflurage massage on breast milk production in postpartum mothers. This study uses a pre-experimental research design with a One Group Pre-Post Test Design. The research was carried out on July 15 - 22, 2019. The research population and sample were 12 respondents with a total sampling technique. The independent variable is efflurage massage and the dependent variable is milk production. Collecting data using observation sheets. Data analysis using McNemar with = (0.05). Research result the 12 respondents, before being given an efflurage massage almost all respondents, namely 10 respondents, breast milk production was not smooth (83.3%), while breast milk production after being given efflurage massage was almost all respondents, namely 11 respondents, breast milk production was smooth (91.7%).test results Mc Nemar obtained p = 0.004 = (0.05), so that Hais accepted. This shows that there is an effect of efflurage massage on breast milk production in postpartum mothers in Kepanjen Village, Pace District, Nganjuk Regency.